2014
DOI: 10.3201/eid2012.140172
|View full text |Cite
|
Sign up to set email alerts
|

TwoAnaplasma phagocytophilumStrains inIxodes scapularisTicks, Canada

Abstract: We developed PCR-based assays to distinguish a human pathogenic strain of Anaplasma phagocytophilum, Ap-ha, from Ap-variant 1, a strain not associated with human infection. The assays were validated on A. phagocytophilum-infected blacklegged ticks (Ixodes scapularis) collected in Canada. The relative prevalence of these 2 strains in I. scapularis ticks differed among geographic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 15 publications
(12 reference statements)
3
35
0
Order By: Relevance
“…phagocytophilum strain types were identified using single-nucleotide polymorphism genotyping assays targeting the 16S rRNA gene as described by Krakowetz et al (2014). Larval ticks from the same host animal were pooled for all testing and analysis; individual nymphs and adults collected by drag sampling were tested.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…phagocytophilum strain types were identified using single-nucleotide polymorphism genotyping assays targeting the 16S rRNA gene as described by Krakowetz et al (2014). Larval ticks from the same host animal were pooled for all testing and analysis; individual nymphs and adults collected by drag sampling were tested.…”
Section: Methodsmentioning
confidence: 99%
“…The Thousand Islands region has been identified as an emerging endemic area for I. scapularis and B. burgdorferi (Werden et al 2014), but the occurrence of other pathogens in ticks in this region has not been fully described. Krakowetz et al (2014) reported that 1.3% of blacklegged ticks from across Canada were positive for A. phagocytophilum. Two strain types of A. phagocytophilum were identified, the human pathogenic strain (AP-ha), which is most often associated with clinical cases of HGA, and a variant strain (AP-variant 1); their relative prevalence appears to vary geographically (Krakowetz et al 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Anaplasmosis is caused by the bacterium Anaplasma phagocytophilum, which is spread by I. scapularis in eastern and central Canada (37) and I. pacificus in British Columbia, and human or animal cases have been reported in most provinces where the ticks occur (38). Clinically, people can have asymptomatic A. phagocytophilum infections, but most frequently have non-specific symptoms (e.g.…”
Section: Anaplasmosismentioning
confidence: 99%
“…Distinct variants not found in humans have been isolated from deer, other ruminants, horses, dogs, and cats, suggesting only a subset of A. phagocytophilum variants cause disease in humans (Lappin et al 2004;Lester et al 2005;Parola et al 2005a;Poitout et al 2005;Morissette et al 2009). More than one strain may be present in a region, and the relative proportion of each strain may vary regionally (Krakowetz et al 2014).…”
Section: Human Granulocytic Anaplasmosis (Hga)mentioning
confidence: 99%